Analisis Hukum Islam Terhadap Paylater Dan Pinjaman Online - Lailan Hafni Damanik; Hanisah Raihanah Larosa; Elis. S Masita Damanik; Ridho Aditya Sembiring; Dava Abie Zandhika Nasution (Albayan Journal of Islam and Muslim Societies, 2026)
The development of digital technology has given rise to various application-based financial services, one of which is paylater and online lending services. The presence of these services provides convenience for society in conducting transactions and obtaining funds quickly without complicated procedures. However, behind this convenience, various problems have emerged, especially those related to interest practices, late payment penalties, and the potential existence of usury (riba) elements that contradict the principles of Islamic law. This study aims to analyze the practices of paylater and online loans from the perspective of Islamic law and to examine their impact on society. The research method used is qualitative research with a normative approach, namely by examining sources of Islamic law such as the Qur'an, Hadith, fiqh principles, and literature related to modern financial transactions. The results of the study indicate that the use of paylater and online loans is basically permissible as long as they fulfill sharia principles, such as clarity of contract, and do not contain riba, gharar (uncertainty), or elements of injustice. However, most conventional paylater and online loan practices still involve interest and penalties that fall into the category of riba, making them generally impermissible according to Islamic law. Therefore, it is necessary to improve Islamic financial literacy and strengthen supervision of digital financial services so that public transactions remain in accordance with the principles of Islamic sharia.